COVID-19 Infection in Children with Leukemia: A Single-center Retrospective Study - Elif Güler Kazancı; Deniz Güven; Rana Yılmaz (Galenos Publishing House, 2023)
Objective: Children were less likely than adults to develop severe illness from coronavirus disease-2019 (COVID-19) infection, whereas children with leukemia had compromised immunity and may be at increased risk of severe COVID-19 infection. The aim of this study is examine the characteristics and outcomes of COVID-19 in children with leukemia. Method: Between March 2020 and February 2021, patients on active leukemia treatment who were diagnosed with severe acute respiratory syndrome coronavirus-2 infection were enrolled in the study. Clinical, laboratory, and radiological characteristics, as well as infection severity and prognosis, were all assessed. Results: The children's median age was 9.6 years, and 66.7 percent of them were male. The majority of patients with COVID-19 infection were in the early stages of leukemia treatment and had severe or critical COVID-19 infection. Six patients were treated for COVID-19. Five patients required oxygen, six were in the intensive care unit, and three were intubated. Twelve patients were fully recovered, and three died. Two of the patients were re-infected with COVID-19. The disease status of re-infected patients was worse than the first infection, and the duration of polymerase chain reaction positivity was much longer. Conclusion: Children with leukemia who have COVID-19 infection may have severe/critical illness. The type and character of primer malignancy, as well as the prognostic factors of COVID-19 infection, may all have an impact on clinical outcomes. It is critical to take the most stringent precautions to prevent infection from spreading to these patients.